PENGARUH FRAUD HEXAGON TERHADAP FRAUDULENT FINANCIAL REPORTING PADA PERUSAHAAN DI INDONESIA - M. Soelung Wicaksono Hadi, (2021)
This research aims empirically the influence of hexagon fraud on fraudulent financial reporting on companies listed in Kompas 100 Index on the Indonesia Stock Exchange in 2016-2019. The selection of samples in this study using purposive sampling method resulted in 184 observations. Hypothesis testing in this study using Multiple Linear Regression Analysis with STATA version 16 application. The results of the data analysis conducted, it can be concluded that (1) pressures projected by financial target has a significant positive effect on fraudulent financial reporting, but for proxies the level of performance has no effect on fraudulent financial reporting, (2) opportunity that are projected by nature of industry has a significant negative effect on fraudulent financial reporting, (3) rationalization that is projected change in auditor has no effect on fraudulent financial reporting, but the proxy ratio of total accrual has a significant positive effect on fraudulent financial reporting, (4) capability that is projected by change on director has no effect on fraudulent financial reporting,(5) arrogance projected by frequent number of CEO photos has no effect on fraudulent financial reporting, and (6) collusion projected political connection has no effect on fraudulent financial reporting.